Stereotactic body radiotherapy as a viable treatment on extracranial oligometastases in melanoma patients: a retrospective multicentric study - Trentesaux, Victorine; Maiezza, Sophie; Bogart, Emilie; Le Deley, Marie-Cécile; Meyer, Emmanuel; Vanquin, Ludovic; Pasquier, David; Mortier, Laurent; Mirabel, Xavier (Frontiers in Oncology, 2024)
Introduction: Stereotactic radiotherapy (SBRT) potentially has a role in the management of oligometastatic melanoma. However, literature with data specific to this management is very limited. The objectives of this study were to evaluate the time to local control (LC) of extracranial melanoma metastases after SBRT treatment and to help establish if SBRT is a useful therapy for oligometastatic melanoma.Methods: A retrospective study was conducted with data collected from two referral centers in France between 2007 and 2020. The oligometastatic status of patients was reported based on the latest recommendations with a maximum of three lesions prior to treatment.Results: A total of 69 patients receiving SBRT for 88 oligometastatic melanoma metastases were included. The median follow-up time was 42.6 months. Most patients were treated for metachronous oligometastatic lesions. Occurrence of oligoprogression, oligorecurrence, and oligopersistence was reported in 42.0%, 39.1%, and 17.4% of cases, respectively. Treated lesions were mostly pulmonary (40.6%), followed by lymph node (34.8%) and hepatic sites (24.6%). Progression-free survival at 1, 2, and 3 years were 47.0% (35-59), 27.0% (16-39), and 25.0% (15.0-37.0), respectively. Time to LC rates at 1, 2, and 3 years were 94.2% (87.0-98.1), 90.3% (81.3-96.1), and 90.3% (81.3-96.1), respectively. Overall survival at 1, 2, and 3 years were 87% (76.0-93.0), 74.0% (76.0-93.0), and 61.0% (47.0-73.0), respectively. Only 17.4% of patients experienced acute, grade 1 or grade 2 toxicities with no reports of grade 3 or higher toxicities.SBRT demonstrated efficacy in managing melanoma patients with extracranial oligometastases and showed an overall low toxicity profile. Future randomized studies are needed to establish the role of SBRT in therapeutic approaches for patients with oligometastatic melanoma.